Advancements in the Treatment of High-Risk Smoldering Myeloma: News from ASH 2024 - Kaveh Samii (healthbook TIMES. Oncology Hematology)
Smoldering multiple myeloma (SMM) is a precursor to symptomatic multiple myeloma (MM), characterized by its asymptomatic yet progressive nature and significant risk of progression. The management of SMM has evolved considerably in recent years with the introduction of targeted therapies. While the traditional "watch and wait" strategy remains the standard approach for low-risk cases, early treatment for high-risk SMM has become increasingly favored, backed by clinical trials highlighting its ability to delay the progression to MM and reduce related complications.